2020
DOI: 10.2174/1386207323666200219121600
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Effects of Astaxanthin on Brain Damage due to Ischemia- Reperfusion Injury

Abstract: Background: Activated inflammation and oxidant stress during cerebral ischemia reperfusion injury (IRI) lead to brain damage. Astaxanthin (ASX) is a type of carotenoid with a strong antioxidant effect. Objective: The aim of this study was to investigate the role of ASX on brain IRI. Methods: A total of 42 adult male Sprague-Dawley rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…For acute cerebral infarction (ACI) rat, the treatment with astaxanthin notably inhibited oxidative stress and increased the mRNA expression of brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF), which led to ameliorate ACI (Table 1) [56]. Astaxanthin also protected the brain from oxidative damage and reduced neuronal deficits due to cerebral ischemia reperfusion injury (IRI) ( Table 1) [57]. The mechanisms of astaxanthin in neuroprotective properties against cerebral ischemia-induced apoptosis were investigated, and the in vitro data revealed that astaxanthin could confer neuroprotection against the oxygen and glucose deprivation (OGD)-induced apoptosis via the PI3K/Akt/GSK3β/Nrf2 signaling pathway (Table 1) [58].…”
Section: The Anti-inflammatory Effects Of Astaxanthin In Neurologicalmentioning
confidence: 99%
“…For acute cerebral infarction (ACI) rat, the treatment with astaxanthin notably inhibited oxidative stress and increased the mRNA expression of brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF), which led to ameliorate ACI (Table 1) [56]. Astaxanthin also protected the brain from oxidative damage and reduced neuronal deficits due to cerebral ischemia reperfusion injury (IRI) ( Table 1) [57]. The mechanisms of astaxanthin in neuroprotective properties against cerebral ischemia-induced apoptosis were investigated, and the in vitro data revealed that astaxanthin could confer neuroprotection against the oxygen and glucose deprivation (OGD)-induced apoptosis via the PI3K/Akt/GSK3β/Nrf2 signaling pathway (Table 1) [58].…”
Section: The Anti-inflammatory Effects Of Astaxanthin In Neurologicalmentioning
confidence: 99%
“…Moreover, it reduces the activity of aldose reductase (AR) which is responsible for the progression of DR [63]. The natural astaxanthin has favorable effects against ischemia-reperfusion injury associated with brain damage and neurovascular inflammation [64]. Commercially, the synthetic glucocorticoid, i.e., DEX, is widely used in various inflammatory and immunological disorders including DR [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…The researchers attributed ASX’s benefits to its intense antioxidant activity. Another study found that pretreatment with ASX for five hours, and again one hour before ischemia, protected against brain damage [ 93 ]. ASX was found to be a potent agent against neurodegenerative disorders.…”
Section: The Role Of Astaxanthin In the Aging Processmentioning
confidence: 99%